Structured Opportunities for Student Physical Activity in Ontario Elementary and Secondary Schools - Allison, Kenneth R. (Can J Public Health, 2000)
This paper examines structured opportunities for student physical activity in Ontario elementary and secondary schools. Random samples of elementary and secondary schools were selected, and telephone surveys of 353 elementary and 360 secondary school personnel were conducted in 1998. The findings indicate that elementary schools offered physical education, on average, just under three days per week. The duration of physical education class and, in some cases, the duration of vigorous physical activity in class and the weekly amount of vigorous activity in class, were significantly higher at successive grade levels. The physical education enrollment rate in secondary schools was significantly lower at successive grade levels. Student participation in secondary school intramurals and inter-school sports was 22.8% and 28.7% respectively. These findings suggest increasing the weekly frequency of physical education in elementary schools and increasing participation in physical education classes in secondary schools. Also, intramural opportunities and participation should be promoted.